Electrically Driven Microengineered Bioinspired Soft Robots. Issue 10 (11th January 2018) - Shin, Su Ryon; Migliori, Bianca; Miccoli, Beatrice; Li, Yi‐Chen; Mostafalu, Pooria; Seo, Jungmok; Mandla, Serena; Enrico, Alessandro; Antona, Silvia; Sabarish, Ram; Zheng, Ting; Pirrami, Lorenzo; et al.
Abstract: To create life‐like movements, living muscle actuator technologies have borrowed inspiration from biomimetic concepts in developing bioinspired robots. Here, the development of a bioinspired soft robotics system, with integrated self‐actuating cardiac muscles on a hierarchically structured scaffold with flexible gold microelectrodes is reported. Inspired by the movement of living organisms, a batoid‐fish‐shaped substrate is designed and reported, which is composed of two micropatterned hydrogel layers. The first layer is a poly(ethylene glycol) hydrogel substrate, which provides a mechanically stable structure for the robot, followed by a layer of gelatin methacryloyl embedded with carbon nanotubes, which serves as a cell culture substrate, to create the actuation component for the soft body robot. In addition, flexible Au microelectrodes are embedded into the biomimetic scaffold, which not only enhance the mechanical integrity of the device, but also increase its electrical conductivity. After culturing and maturation of cardiomyocytes on the biomimetic scaffold, they show excellent myofiber organization and provide self‐actuating motions aligned with the direction of the contractile force of the cells. The Au microelectrodes placed below the cell layer further provide localized electrical stimulation and control of the beating behavior of the bioinspired soft robot. Abstract : A bioinspired robot is designed and fabricated by mimicking the biomechanical model of a batoid fish, which is composed of two micropatterned hydrogel layers and flexible microelectrodes to induce driving the contractions of the soft robot by electrical stimulation. The bioinspired robot shows actuation aligned with the direction of the contractile force of the cells.